Rancangan Aplikasi Manajemen Dokumen Tender Berbasis Web Pada PT. Emi - Yusuf, Sablin (Bina Nusantara University, 2010)
The objective of this researh is to design a software application for bidding document management as required by PT Energy Management Indonesia (EMI) in order to increase the company performance. The methodology used is fact-finding through direct observation, followed by literature study, and web application development method using waterfall model and rapid prototyping for software development. The result is a software application, web based, which can increase the company performance due to the required bidding document preparation and the responding data are well stored and managed hence can be accessed easily when needed. In summary the application which is well supported by the related database will assist the company quikly and easily in bidding preparation process